ANALISIS PADA FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PEMBANGUNAN MANUSIA DI SUMATERA UTARA MENGGUNAKAN SPATIAL DURBIN MODEL - Ayu Lestari; Machrani Adi Puteri Siregar; R Maisaroh Rezykiyah Siregar (LPPM Universitas Bina Bangsa, 2024)
The Human Development Index (HDI) is one of the important indicators in development. Some of the factors that influence the Development Index in North Sumatra in 2021 are the percentage of toddlers who have received measles immunization, the percentage of the population who have health complaints during the last month, the percentage of the population who have health insurance BPJS contributions, the percentage of the population who are still in school with the age group 7-15 years, the percentage of pure high school enrollment rate, the percentage of poor people, the percentage of labor force participation rate of the population aged 15 years and over, and the percentage of open unemployment rate of the population aged 15 years and over. The purpose of this study is to determine the factors that have a significant effect on the Human Development Index in North Sumatra. In this study using Spatial Durbin Model (SDM) which is a special case of Spatial Autoregressive (SAR) by adding the effect of lag on the independent variable so that spatial lag is added to the model, weighting is done on the independent and dependent variables. The results obtained show that the factors that have a significant effect on the Human Development Index (HDI) in North Sumatra in 2021 are the percentage of the population who are still in school with the age group 7-15 years (X4), the percentage of the Pure High School Enrollment Rate (X5), the Percentage of Labor Force Participation Rate of Population 15 Years and Over (X8).